Liminalities and Displacements: The Rites of Passage to Self-Identification in Chicano Writings - Sophia Emmanouilidou (Revue LISA)
The aim of this paper is to explore the hermeneutics of selfhood under conditions of excruciating socio-political injustice, and to detect the rites of passage to self-conceptualization as unravelled in two Chicano literary writings: Tomás Rivera’s “…y no se lo tragó la tierra” (1971) and Tino Villanueva’s Scene from the Movie GIANT (1993). The purpose of this approach is to show how two different literary genres, namely a collection of vignettes and a book-length poem, tackle the problems of adolescent liminalities through the prism of Chicano experience in the borderlands. The two masterful texts present truthful and shocking testimonials of the inner conflicts endured by young Mexican-Americans toiling over the soil or experiencing marginalization in the back-row seat of a movie theatre in their attempt to carve a third space of existence among migrant campesinos and barrio inhabitants. Rivera and Villanueva venture bold explorations of the self-regulatory rites to ethnic identity, and provide the readers with stunning insights into the liminal aspects of identity, as realized in the contexts of discrimination and social oppression, and en route to an esoteric understanding of life.